İş sözleşmesinin devri - Kutbay, Nurgül (My University, 2019)
“İş Sözleşmesinin Devri” kurumu kanun koyucu tarafından ilk kez 6098 sayılı Türk Borçlar Kanunu (“TBK”) m. 429 ile düzenlenmiştir. Söz konusu düzenleme ile birlikte iş sözleşmesinin devri pozitif hukukta yerini almıştır. İş sözleşmesinin devri kurumu İş Kanunu’nda ayrı bir düzenleme olarak bulunmamaktadır. Çalışmamızda da iş sözleşmesinin devri kurumu üç bölümde ele alınmıştır. Çalışmamızın birinci bölümünde kanun koyucunun TBK m. 205 ile düzenlemiş olduğu sözleşmenin devri kurumu ele alınmıştır. Zira her türlü sözleşmenin devrine ilişkin genel kanun hükmü niteliğinde olan bu düzenleme iş sözleşmesinin devri kurumuna da uygulanabilecektir. İkinci bölümde ise iş sözleşmesinin devri kavramı ele alınarak iş sözleşmesinin devri kurumunun tanımı, hukuki geçerlilik şartları, benzer hukuki ilişkiler ile karşılaştırılmaları gerçekleştirilmiştir. Çalışmamızın üçüncü bölümünde ise geçerli olarak devredilen bir iş sözleşmesinin sonuçları ele alınmıştır. Söz konusu sonuçlar; bireysel iş hukuku, toplu iş hukuku, sosyal güvenlik hukuku, kişisel verilerin korunması hukuku ve iş sağlığı ve güvenliği hukuku açısından ayrı ayrı ele alınmıştır. Çalışmamızın sonuç kısmında ise çalışmamızın genel değerlendirmesi yapılmıştır.

For the first time, the subject of “Transfer of Employment Contract was legislated by the legislator with the article 429 of Turkish Code of Obligations numbered 6098 (“TCO”). The subject of transfer of employment contract has been officially taken place in the law with this legal arrangement. The transfer of the employment contract is not as a separate arrangement in the Labour Law. In this study, the aforementioned subject was discussed in three sections.In the first part of this study, the subject of transfer of the contract regulated in Article 205 of TCO has been taken into consideration. This regulation, which is the provision of the general law on the transfer of all kinds of contracts, can also be applied to the transfer of employment contract. In the second part, the term of the transfer of employment contract was taken into consideration and the definition of the transfer of employment contract, legal validity conditions, the comparison with similar legal relations were made. In the third part of our study, the results of a legally transferred employment contract were discussed. These results are discussed separately in terms of individual employment law, collective employment law, social security law, personal data protection law and occupational health and safety law. In the conclusion part of this study, the general evaluation of the study was made.
Keywords: Contracts; Hukuk; İş Sözleşmesi Devrinin Sonuçları Transfer of the Contract; İş Sözleşmesinin Devri; Law; Results of the Transfer of Employment Contract; Sözleşmeler; Sözleşmenin Devri; Transfer of Employment Contract